Patient factors influencing inappropiate antibiotic prescribing for upper respiratory tract infection (URTI) in Emergency Department, Hospital Universiti Sains Malaysia - Ahmad, Azmi (2020)
Introduction Upper respiratory tract infection (URTI) is a common clinical presentation for nonemergency cases in the emergency department. Increased numbers of the non-emergency cases such as URTI may contribute to inappropriate antibiotic prescribing. Most of the study done in Malaysia regarding URTI was done in the outpatient department. The objective of this study is to determine patient factors associated with inappropriate antibiotic prescribing for URTI in emergency department Hospital USM. Methods This was an observational, cross sectional study involving patients diagnosed as URTI admitted in the green zone in the emergency department of a tertiary teaching hospital in the east coast of Malaysia. Data collected included patient’s demography (age, gender, race), duration of illness, working days, working shift, frequency of health visit, patient’s symptom and signs. Patients were categorized into two groups: positive McIsaac (score ≥2) and negative McIsaac (score <2). Factors associated in influencing antibiotic prescribing in the negative McIsaac group (inappropriate prescription) were determined. Results A total of 261 subjects were included. There were 127 positive and 134 negative McIsaac score. From the total, most common URTI symptoms presented were fever (85%) and cough (76%). Highest antibiotic prescriptions were for acute tonsillitis and acute pharyngitis (42% and 36% respectively). Both groups showed higher prescription of amoxicillin (33%) and amoxicillin/clavulanate acid (34%). The overall inappropriate antibiotic prescribing based on negative McIsaac score was 29%. Duration of symptoms, symptoms of chill and specific diagnosis of acute tonsillitis were associated with inappropriate antibiotic prescription. Conclusion Emergency doctors should be aware of the influence of patient’s symptom and specific final diagnosis in prescribing antibiotic for URTI. The occurrence of inappropriate antibiotic prescribing in the emergency department can still be improved with intervention to re-educate, retraining and academic detailing which address prescribers regarding the importance of scoring system coupled with good clinical assessment in managing URTI.